The Mexican rescue - Kraft, Joseph (New York : Group of Thirty, 1984)
It is a journalist's account of what actually happened after the Mexican bombshell dropped on the world's banking system in August 1982. It describes how the major institutions of the international monetary system responded to the challenge. It shows in dramatic form and perhaps for the first time the extraordinary range of difficulties, misunderstandings and personality conflicts that have to be managed in the course of such an operation. In the words of the author, this is the story of the Mexican rescue.
ne 15/04/2019
Loans
Keywords: Debts, External; Loans, Foreign; International finance; Mexico